Implementasi Pembelajaran Takror dalam Menguatkan Hafalan Santri TPQ Program Tahfidz Masjid Besar Az-Zuhud Petanahan Kebumen - Husnul Khotimah; Ngarifin Shidiq; Nur Farida (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to understand the concept of takror learning in strengthening students' memorization, to examine the implementation of takror learning in strengthening the memorization of students in the tahfidz program of TPQ at the Great Mosque of Az-Zuhud, Petanahan, Kebumen, and to identify the supporting and inhibiting factors of takror learning in the tahfidz program of TPQ at the Great Mosque of Az-Zuhud, Petanahan, Kebumen. This research uses a qualitative field method with interview and observation techniques. The results of the study indicate that the concept of takror learning implemented at the TPQ tahfidz program of the Great Mosque of Az-Zuhud, Petanahan, Kebumen is intended to strengthen students’ memorization. Takror learning is divided into two types: classical and individual. The process of takror learning also involves several stages. The takror learning implemented in the tahfidz program at TPQ of the Great Mosque of Az-Zuhud, Petanahan, Kebumen is carried out individually and classically. Individual learning is applie d after classical learning is completed, where students review their memorization and receive guidance from an ustadz (male teacher) or ustadzah (female teacher). Meanwhile, classical learning is conducted by collectively reviewing memorization in front of the ustadz or ustadzah. The factors supporting the implementation of takror learning there include time availability and the presence of PKBM (Community Learning Activity Center) activities. In contrast, the inhibiting factors are mostly related to age, which makes it difficult for students to manage their time during the learning process